Diagnosis and Management of Subcoracoid Impingement. Issue 3 (1st February 2021) - McKernan, Michael J.; Schickendantz, Mark S.; Frangiamore, Salvatore J.
Abstract : Impingement of the subcoracoid space is a poorly understood pathologic cause of anterior shoulder pain. Because of its relative rarity in isolation and nonspecific presentation, diagnosis and management are often challenging for orthopaedic surgeons and their patients. Stenosis of the subcoracoid space between the lesser tuberosity and the coracoid process <6 mm can lead to anterior shoulder pain and associated rotator cuff and biceps pathology. Multiple imaging modalities are available to assess narrowing of the coracohumeral interval, each with its strengths and limitations. If the patient can be accurately diagnosed with subcoracoid impingement, both conservative and surgical management options are available. Despite earlier case series demonstrating promising results with arthroscopic treatment, comparative studies have yet to support these initial claims.